2016
DOI: 10.1038/srep27548
|View full text |Cite
|
Sign up to set email alerts
|

M2-polarized macrophages contribute to neovasculogenesis, leading to relapse of oral cancer following radiation

Abstract: Despite the fact that radiation is one of the standard therapies in the treatment of patients with oral cancer, tumours can recur even in the early stages of the disease, negatively impacting prognosis and quality of life. We previously found that CD11b+ bone marrow-derived cells (BMDCs) were recruited into human glioblastoma multiforme (GBM), leading to re-organization of the vasculature and tumour regrowth. However, it is not yet known how these cells contribute to tumour vascularization. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 46 publications
2
54
0
Order By: Relevance
“…The polarization of TAMs toward M1 phenotype upon inhibition of EphB4-ephrin-B2 is most evident when combined with RT. In oral cavity cancers, the recolonization of tumors by M2-like macrophages post-RT has also been shown to elicit the secretion of pro-angiogenic factors that contribute to neo-angiogenesis, favoring tumor regrowth (61). In our HNSCC model, we show that the combined treatment with an EphB4-ephrin-B2 inhibitor and RT decreases macrophages with the M2 phenotype.…”
Section: Discussionmentioning
confidence: 57%
“…The polarization of TAMs toward M1 phenotype upon inhibition of EphB4-ephrin-B2 is most evident when combined with RT. In oral cavity cancers, the recolonization of tumors by M2-like macrophages post-RT has also been shown to elicit the secretion of pro-angiogenic factors that contribute to neo-angiogenesis, favoring tumor regrowth (61). In our HNSCC model, we show that the combined treatment with an EphB4-ephrin-B2 inhibitor and RT decreases macrophages with the M2 phenotype.…”
Section: Discussionmentioning
confidence: 57%
“…This method, however, is only recommended for formalin‐fixed paraffin embedded (FFPE) and resin embedded samples since their tissue morphology are usually very well‐preserved. Recent studies have reported that M2‐polarized macrophages promoted angiogenesis as well as vasculogenesis . Yet on the other hand, there are studies that showed M1‐polarized macrophages to be able to promote angiogenesis as well, secreting VEGF and stimulating endothelial cell sprout formation both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In this study there was no impact of VEGFR2 knockout on haematopoietic cell populations. An impact of this knockout system on circulatory macrophages and consequent endothelium would be expected to be minimal as there is a very small number of, if any, Tie2-positive, VEGFR2-positive macrophages (Okubo et al 2016).…”
Section: Discussionmentioning
confidence: 99%